2014
DOI: 10.2478/s11535-014-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Leucojum aestivum L. in vitro bulbs induction and acclimatization

Abstract: Abbreviations:ANC -ancymidol; FW -fresh weight; GA 3 -gibberellic acid; LM -liquid medium; MS -Murashige and Skoog basal medium; PBZ -paclobutrazol; SCR -sucrose; SEM -scanning electron microscopy; SM -solid medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In terms of bulbing ability in bulbous plants, Rice et al (1983) enhanced tulip bulb production in vitro by soaking adventitious shoots developed into a bulb in GA 3 . In contrast, treatments with GA 3 in explant shoots strongly inhibited the bulb formation of tulips in a study reported by Podwyszy nska and Ross (2003), and the application of inhibitors of GA biosynthesis, such as paclobutrazol, had a positive effect on bulb formation in initial explants of some bulbous plants including Leucojum aestivum (Ptak, 2014) and tulip (Podwyszy nska, 2006). ABA was found to stimulate the formation of bulb in Hyacinthus orientalis (Li et al, 2002).…”
mentioning
confidence: 75%
“…In terms of bulbing ability in bulbous plants, Rice et al (1983) enhanced tulip bulb production in vitro by soaking adventitious shoots developed into a bulb in GA 3 . In contrast, treatments with GA 3 in explant shoots strongly inhibited the bulb formation of tulips in a study reported by Podwyszy nska and Ross (2003), and the application of inhibitors of GA biosynthesis, such as paclobutrazol, had a positive effect on bulb formation in initial explants of some bulbous plants including Leucojum aestivum (Ptak, 2014) and tulip (Podwyszy nska, 2006). ABA was found to stimulate the formation of bulb in Hyacinthus orientalis (Li et al, 2002).…”
mentioning
confidence: 75%
“…After 3 months of cultivation, plantlets were transferred to the same fresh medium. The formations of bulblets took place at 5°C in the darkness during 1 month according to the method previously described .…”
Section: Methodsmentioning
confidence: 99%
“…The growth and size of bulb depend upon the distribution of carbohydrates in root and shoot of a plant. The supplementation of bulblets with sucrose and growth retardants like paclobutrazol exogenously in the culture medium affects the bulb size under in vitro conditions (Saos et al, 2002;Ptak et al, 2014). As a known inhibitor of gibberellin biosynthesis, paclobutrtazol retard shoot elongation and lead to an increase in the root-to-shoot ratio (bulb weight) by translocation of assimilates from the leaves to the storage organs in various bulbous and tuberous species (Li et al, 2014;Yan et al, 2011;Harvey et al, 1991).…”
Section: Introductionmentioning
confidence: 99%